DAMPAK PERKEMBANGAN ILMU FALAK PADA MASA DINASTI ABBASIYAH - Shafira Amajida; Nurul Izza (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The progress of Falak science during the Abbasiyah dynasty had a huge impact on contemporary science. The influence of Greek, Persian and Indian civilizations provided very significant developments. The translation of books carried out during the Al-Makmun’s government made things easier for thinkers of that time. The institutions established and the facilities provided by the government have had a huge impact in leading to the birth of leading scientists. The purpose of this article is to explain the impact of historical developments during the Abbasid dynasty on the development of astronomy today. This research is qualitative research using the library research method. The approach used is socio-historical analysis which focuses on historical narration with a focus on a certain period. The data collection technique used is documentation of primary data and secondary data.